Selected Short Stories of Anita Agnihotri: Mysterious Anecdotes of Marginal Life/ অনিতা অগ্নিহোত্রীর নির্বাচিত ছোটগল্প : প্রান্তিক জীবনের মরমী উপাখ্যান (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
The short story is one of the most modern branch of Bengali Literature and one of the art forms of creative prose. Since its birth, this branch of literature has gradually spread beyond the borders of the country and time by collecting material from within the known geographical limits. Literary Anita Agnihotri herself has traveled to different parts of East and central and northern Odisha came close to the marginal people. She has given shape to the story of the life of the people there, the story of their constant struggle for survival in daily life their. She was able to realize very closely the reality of the marginal society living close to the soil. The various crises of society, the lack of hunger, the life of marginal people and social injustice has beautifully shown in Anita Agnihotri’s writing. The writer has planted one seed in the form of stories while talking about the diffrent regions and different people of India, their lifestyle, language manners, and various short comings of livings. The basis of all these stories in mainly about the environment, nature and people outside Bengal. Village, urban underclasses, water bodies, rivers, forests and lost township and their pathetic stories emerge in Anita Agnihotri’s stories.
Keywords: Geographical; central; survive; regions; injustice